Sharing vesicles between central presynaptic terminals: implications for synaptic function - Staras, Kevin; Branco, Tiago (Frontiers in Synaptic Neuroscience, 2010)
Presynaptic terminals in hippocampal neurons house functionally distinct vesicle pools, the size, structure and biochemical features of which are major determinants of presynaptic strength and performance. In classical models of synaptic function these vesicle pools are synapse-specific, but accumulating evidence is now demonstrating that some vesicles are laterally mobile along axons and readily shared in a functional manner across adjacent terminals. In effect then, these mobile vesicles represent a further class of synapse-spanning vesicle pool, or “superpool”. Here we outline the characteristics of this additional pool type, discussing its structural organization within axons and presynaptic terminals as well as its relationship with conventional vesicle pools. We draw comparisons between extrasynaptic vesicle dynamics and the growing literature on extrasynaptic mobility of non-vesicular synaptic elements which, taken together, raise important questions about the operational independence of adjacent release sites. We also examine the functional implications of lateral vesicle sharing, from the notion that extrasynaptic vesicles can contribute to the release capabilities of individual terminals, to its potential role as a substrate for facilitating changes in synaptic weight as a basis for plasticity.